2011
DOI: 10.1007/s11661-011-0622-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb Microalloying and Hot Rolling on Microstructure and Properties of Ultrathin Cast Strip Steels Produced by the CASTRIP® Process

Abstract: The microstructure and corresponding tensile properties of both plain and Nb-microalloyed grades of ultrathin cast strip (UCS) low alloy steel produced using the CASTRIP Ò process were studied. Both as-cast and hot-rolled strip cast steels with various levels of Nb microalloying were manufactured and investigated in this study. Hot rolling had little effect on the yield strength of Nb microalloyed UCS specimens for a given chemical composition, but resulted in a slightly finer microstructure. The effect of Nb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It was found that in low carbon steel (~0.03% C, ~0.85% Mn and 0.2% Si), a 0.084% Nb addition would increase the yield strength of hot-rolled strips by 20-30%. 17,25) This strengthening is attributed to niobium's effect in promoting bainite and acicular ferrite formation during austenitic transformation, as well as the formation of Nb-N clusters. 17,25) …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that in low carbon steel (~0.03% C, ~0.85% Mn and 0.2% Si), a 0.084% Nb addition would increase the yield strength of hot-rolled strips by 20-30%. 17,25) This strengthening is attributed to niobium's effect in promoting bainite and acicular ferrite formation during austenitic transformation, as well as the formation of Nb-N clusters. 17,25) …”
Section: )mentioning
confidence: 99%
“…17,25) This strengthening is attributed to niobium's effect in promoting bainite and acicular ferrite formation during austenitic transformation, as well as the formation of Nb-N clusters. 17,25) …”
Section: )mentioning
confidence: 99%
“…Cooling rates of 10 2 to 10 4 °C/s are typically encountered during strip casting and the information on castability of different alloys under rapid solidification conditions have been largely gathered either by characterization of industrial scale strip cast products [3][4][5][6][7][8][9][10] or by carrying out targeted experiments with techniques such as levitation droplet melting and solidification, [11][12][13][14] and/or immersion solidification testing using a specially designed dip tester. [15][16][17][18][19][20] The dip tester 15) is based on the principle of rapidly submerging a copper substrate into a bath of molten metal, with a liquid-solid contact time of around 0.2 s. Thermocouples embedded below the substrate surface measure the temperature response of the substrate with millisecond resolution, and these measurements are used to calculate instantaneous heat flux during solidification.…”
Section: Background On Strip Casting Of Steelsmentioning
confidence: 99%
“…[15] To add to the complexity, similar systems with small variations in composition can result in steels with different microstructures and/or mechanical properties. [17] For instance, addition of only 0.08 wt pct Nb altered the austenite-ferrite transformation temperature, thereby the microstructure resulting iñ 30 pct increase in yield strength. [17,18] This brief overview illustrates how the type and amount of alloying elements control the mechanical properties in multi-microalloy steel through microstructure control and precipitation.…”
Section: Introductionmentioning
confidence: 99%